Pattern of skin infections in black Africans of Sierra Leone (West Africa) - Bari Arfan ul (Wolters Kluwer Medknow Publications, 2007)
Background: Physical differences among human populations may lead to variable prevalence of skin disorders in different ethnicities. Skin infections are one of the important curable and largely preventable categories of skin disorders in the communities. Aim: The purpose of the study was to see the patterns of skin infections in black Africans of Sierra Leone and to compare with other ethnic populations. Materials and Methods: Local blacks of all age groups presenting in Dermatology out patient department of Pak Field Hospital (established as a part of UN peacekeeping mission in Sierra Leone) were included (from Nov 2004 to Oct 2005). Relevant clinical history and physical examination was done. Laboratory investigations were carried out when indicated. Skin diseases were broadly classified into two major categories i.e., infective and noninfective. Among infective, sexually transmitted infections were again separated. Nonblack settlers in the area and UN troops were not included in the study. Data was recorded and analyzed by Microsoft Excel program. Results: 3011 patients belonging to different local tribes having a variety of skin disorders were seen. Patients were of all ages and both sexes ranging from one month to 73 years of age. The Infective skin disorders were seen in 61.7% patients and most prevalent were superficial fungal infections (41.2%) followed by, sexually transmitted infections (9.9%) and parasitic infections (6.5%). Bacterial and viral infections were rare and so was the scabies. More than 90% parasitic infections were onchocerciasis with full spectrum of cutaneous manifestations. Conclusion: Pattern of skin infections in blacks varies considerably from other ethnic races. Environmental factors, geographical location and free existence of vector for onchocerciasis in West African region, possibly have a significant influence in this variable prevalence.